Parasite-dependent expansion of TNF receptor II-positive regulatory T cells with enhanced suppressive activity in adults with severe malaria. - Gabriela Minigo (PLoS Pathogens, 2009)
Severe Plasmodium falciparum malaria is a major cause of global mortality, yet the immunological factors underlying progression to severe disease remain unclear. CD4(+)CD25(+) regulatory T cells (Treg cells) are associated with impaired T cell control of Plasmodium spp infection. We investigated the relationship between Treg cells, parasite biomass, and P. falciparum malaria disease severity in adults living in a malaria-endemic region of Indonesia. CD4(+)CD25(+)Foxp3(+)CD127(lo) Treg cells were significantly elevated in patients with uncomplicated (UM; n = 17) and severe malaria (SM; n = 16) relative to exposed asymptomatic controls (AC; n = 10). In patients with SM, Treg cell frequency correlated positively with parasitemia (r = 0.79, p = 0.0003) and total parasite biomass (r = 0.87, p<0.001), both major determinants for the development of severe and fatal malaria, and Treg cells were significantly increased in hyperparasitemia. There was a further significant correlation between Treg cell frequency and plasma concentrations of soluble tumor necrosis factor receptor II (TNFRII) in SM. A subset of TNFRII(+) Treg cells with high expression of Foxp3 was increased in severe relative to uncomplicated malaria. In vitro, P. falciparum-infected red blood cells dose dependently induced TNFRII(+)Foxp3(hi) Treg cells in PBMC from malaria-unexposed donors which showed greater suppressive activity than TNFRII(-) Treg cells. The selective enrichment of the Treg cell compartment for a maximally suppressive TNFRII(+)Foxp3(hi) Treg subset in severe malaria provides a potential link between immune suppression, increased parasite biomass, and malaria disease severity. The findings caution against the induction of TNFRII(+)Foxp3(hi) Treg cells when developing effective malaria vaccines.